Photovoltaic design & installation for dummies - Mayfield, Ryan (--For dummies., 2019)
Photovoltaic Design and Installation For Dummies (9781119544357) was previously published as Photovoltaic Design and Installation For Dummies (9780470598931). While this version features a new Dummies cover and design, the content is the same as the prior release and should not be considered a new or updated product. The fun and easy way to get a grip on photovoltaic design and installation Designing and installing solar panel systems is a trend that continues to grow. With 'green collar' jobs on the rise and homeowners looking for earth-friendly ways to stretch their dollars and lesson their carbon imprint, understanding photovoltaic design and installation is on the rise. Photovoltaic Design & Installation For Dummies gives you a comprehensive overview of the history, physics, design, installation, and operation of home-scale solar-panel systems. You'll also get an introduction to the foundational mathematic and electrical concepts you need to understand and work with photovoltaic systems.-Covers all aspects of home-scale solar-power systems -Viable resource for professionals, students, and technical laymen -Can be used to study for the NABCEP exam Whether you're a building professional looking to expand your business and skills to meet the growing demand for solar power installation or are seeking a career in this rapidly expanding field, Photovoltaic Design & Installation For Dummies has you covered!